2005
DOI: 10.1002/elan.200503275
|View full text |Cite
|
Sign up to set email alerts
|

EQCM Study of Iridium Anodic Oxidation in H2SO4 and KOH Solutions

Abstract: In the present study anodic oxidation of iridium layer formed thermally on a gold-sputtered quartz crystal electrode has been investigated by electrochemical quartz crystal microgravimetry (EQCM) in the solutions of 0.5 M H 2 SO 4 and 0.1 M KOH. The emphasis here has been put on the microgravimetric behavior of iridium as a metal, because a few previous EQCM studies reported in literature have been devoted to iridium oxide films (IROFs). The objective pursued here has been to elucidate the nature of the main v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…It is the same for anodic and cathodic processes, what points to the reversible character of the process. Similar values of Dm/DQ were reported for other Pt group metals as well [15,16,24]. Characteristic feature of Df À E profiles in Figure 2b is the fact that the mass of the electrode continuously increases, i.e., the initial mass of the electrode at the end of the cycle is about ca.…”
Section: Resultssupporting
confidence: 83%
“…It is the same for anodic and cathodic processes, what points to the reversible character of the process. Similar values of Dm/DQ were reported for other Pt group metals as well [15,16,24]. Characteristic feature of Df À E profiles in Figure 2b is the fact that the mass of the electrode continuously increases, i.e., the initial mass of the electrode at the end of the cycle is about ca.…”
Section: Resultssupporting
confidence: 83%
“…This observation supports previous electrochemical studies, whereby Ir III /Ir IV transition was postulated but not spectroscopically confirmed in situ . 24 , 25 , 40 42 …”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…43 The mechanism of the Ir-oxide growth has been investigated in detail before. [44][45][46][47] The basis of the widely accepted hypothesis is that anodic oxidation of noble metals is believed to take place on the surface of the non-oxidized iridium electrode via chemisorption of OH radicals and O atoms. According to ref.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%